1986
DOI: 10.1002/jcp.1041270312
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of RNA polymerase type II from human term placenta

Abstract: RNA polymerase type II from human term placenta has been isolated and characterized with respect to its template, ammonium sulfate, divalent cation, and buffer preferences. In addition, the apparent Michaelis constants for AMP and UMP incorporation have been determined. The enzyme was also analyzed by native and denaturing polyacrylamide gel electrophoresis, and evidence is presented that a single polypeptide is radiolabeled with azido purine nucleoside triphosphate photoprobes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Because of this extraordinary level of evolutionary conservation, the plasmid shuffle experiment revealed that the human subunit is also fully functional in S. cerevisiae. Human RNA polymerase II appears have at least nine subunits (16), two of which are large (-200 and -150 kDa) and seven of which are small (<50 kDa). The genes encoding human subunits related to yeast RPB1, RPB3, RPB5, and RPB9 have been isolated (1,10,25,26).…”
Section: Resultsmentioning
confidence: 99%
“…Because of this extraordinary level of evolutionary conservation, the plasmid shuffle experiment revealed that the human subunit is also fully functional in S. cerevisiae. Human RNA polymerase II appears have at least nine subunits (16), two of which are large (-200 and -150 kDa) and seven of which are small (<50 kDa). The genes encoding human subunits related to yeast RPB1, RPB3, RPB5, and RPB9 have been isolated (1,10,25,26).…”
Section: Resultsmentioning
confidence: 99%
“…While a number of groups have purified human pol II and associated proteins (26,32,36,45,51; also reviewed in references 57 and 70), it has been clear from a comparison of results that the number, molecular weight, and quantity of copurified proteins are somewhat variable between different groups and starting sources of material, and it was previously uncertain whether a human RPB4 homolog existed. The ϳ27 kDa hsRPB7 species and ϳ18-to 19-kDa native hsRPB4 species described in this work are now shown to be present in affinity-purified pol II, conclusively demonstrating their functionality in mammalian cells.…”
Section: Conservation Of Hsrpb4 Mmrpb4 and Rpb4 Subunitsmentioning
confidence: 99%
“…Upon biochemical purification, human pol II appears have at least nine subunits (8), two large (ϳ200-and 150-kDa) and seven small (Ͻ50-kDa) subunits. However, human pol II is likely have at least as many subunits as the 12-subunit yeast S. cerevisiae enzyme since all 12 human genes related to the yeast subunits have now been identified.…”
Section: Resultsmentioning
confidence: 99%
“…It is still unclear whether these 12 human pol II subunits represent the complete set of subunits. Human pol II is relatively poorly defined at the biochemical level (8). Therefore, the precise number of human RNA polymerase subunits that copurify with in vitro transcription activity is not known.…”
Section: Resultsmentioning
confidence: 99%